Communication Strategy in Handling Customer Complaints in PDAM Tirta Pakuan Bogor - Raden Isma Anggraini; Fithriyyah Shalihati; Muchamad Bachtiar; suhendi (School of Business, IPB University (SB-IPB), 2020)
This study aims to 1) identify complaints that arise and do not satisfy customers, and 2) identify communication strategies undertaken by PDAM Tirta Pakuan in handling customer complaints. The study was conducted at PDAM Tirta Pakuan using qualitative descriptive analysis. Researchers surveyed customers and held focus group discussions with the management of PDAM Tirta Pakuan. The method of data analysis is done by using a gap analysis between performance and the interests/expectations of customers for product and service attributes, as well as public relations strategy theory. The results showed that there were four attributes that predominantly received complaints and were not yet satisfying customers, namely the quality of water flow in the dry season, replacement or re-measurement of water meters, compensation for service interruptions, and compensation for settlement of claims for paying bills. Furthermore, there are four communication strategies that are carried out in handling customer complaints based on four aspects, namely fact-finding, planning and programming aspects, action and communication aspects, and evaluating aspects. Some things that need attention from the management of PDAM Tirta Pakuan are 1) improving the quality of water supply during the dry season, 2) periodically replacing or repeating water meters, 3) improving the compensation system for customer service interruptions, 4) improving the compensation system related to the problem of settling claims for payment of claims, 5) identifying complaints that have the potential to threaten the image or reputation of the company, 6) maximizing the use of social media in informing work activities that have the potential to cause service disruptions and customer complaints. Keywords: communication strategies, customer complaints, public relations, service disruption, social media